Solution of the inverse problem of tracer tests interpretation results for oil reservoirs in the presence of low resistance channels - Konstantin M. Fedorov; Alexander Y. Gilmanov; Alexander P. Shevelyov; Aleksey A. Izotov; Alexander V. Kobyashev (Вестник Самарского университета: Естественнонаучная серия)
Tracer tests of oil reservoirs have become widely used to assess the parameters of low resistance channels, leading to premature increasing of production water cut. The existing analytical methods of their interpretation do not consider the dissipation of the tracer. The article proposes a methodology of tracer tests interpretation in the presence of low resistance channels, which considers the configuration of the tracer slug in the producer. The developed method is based on solving the inverse problem of tracer filtration in the low resistance channel and for the first time considers its dissipation. The formulation of the inverse problem of tracer filtration in the low resistance channel is based on the use of the tracer transfer equation in the channel, the ratio for the reagent flow in the channel and the reservoir, Darcy’s law and the relationship of the volume of the tracer slug with its linear size. The algorithm of numerical determination of the tracer dissipation coefficient by solving the optimization problem by the gradient descent is given. The developed algorithm has been tested on the example of the tracer tests interpretation for two producers of one of the Western Siberia fields. The lengths of each channel for the selected wells are determined. It is shown that the error of comparison of calculated and field data does not exceed 7%. It was found that the length of the shortest channel corresponds to the distance between injector and producer, other channels have a longer length and can be formed later.